Perancangan Sistem Portable Solar Water Pump Pada Kebun Buah Dan Sayur - Saputra, Rendy, Aris Budiman, S.T., M.T (2016)
Portable solar water pump system use solar panels to convert solar energy into electrical energy. The electrical energy is used to drive load of water pump. The ricultural sector is currently utilizing alternative energy optimally in particular the utilization of energy from sunlight. In the paper, writer provide a solution in the form of rtable system design solar water pump to help farmers in the process of watering the garden with a relatively expensive cost. Design of portable solar water pump system use solar panel is designed to be easy to carry to the plantation of fruit and vegetable. The water pump can work from 09.00 am to 15.00 pm, the pump can work optimal from 10.00 am till 14.00 pm and the pump is not working optimally at 09.00 am till 10.00 am and 14.00 pm till 15.00. The ability of the portable solar water pump system is very dependent on the intensity of sunlight, the State of the Earth's atmosphere that clouds, dust, smoke, moisture and wind speed around the solar panels. The results obtained upon the condition of low voltage with 9,7 volt and current 5,29 ampere at light intensity 438 lux, in the highest condition with voltage 10,8 volt and current 6,25 ampere at light intensity 803 lux. Portable solar water pump system can work properly it needs to be applied on a large scale in order to work more effectively.